1998
DOI: 10.1046/j.1365-2222.1998.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term oral treatment with leflunomide on allergic sensitization, lymphocyte activation, and airway inflammation in a rat model of asthma

Abstract: Leflunomide prevents antigen-specific immunoglobulin production after sensitization during treatment, inhibits allergen-induced airway inflammation and diminishes antigen-specific T lymphocyte proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In the rat, Th1 cytokines favor the generation of IgG2a and IgG2b immunoglobulins, whereas under the influence of Th2 cytokines, IgG1 antibodies are preferentially produced. 47,48 Similar to our findings in the EAE model, lymph node T cells from superTGR rats secreted high levels of IL-4 and reduced amounts of IFN␥ after intranasal challenge with ovalbumin (data not shown). To investigate whether this Th2 bias impacts the production of ovalbumin-specific antibodies, we followed their time course in the serum over the time period of immunization.…”
Section: Isotype Switching Is Altered In Supertgr Ratssupporting
confidence: 83%
See 1 more Smart Citation
“…In the rat, Th1 cytokines favor the generation of IgG2a and IgG2b immunoglobulins, whereas under the influence of Th2 cytokines, IgG1 antibodies are preferentially produced. 47,48 Similar to our findings in the EAE model, lymph node T cells from superTGR rats secreted high levels of IL-4 and reduced amounts of IFN␥ after intranasal challenge with ovalbumin (data not shown). To investigate whether this Th2 bias impacts the production of ovalbumin-specific antibodies, we followed their time course in the serum over the time period of immunization.…”
Section: Isotype Switching Is Altered In Supertgr Ratssupporting
confidence: 83%
“…In contrast, superTGR rats completely failed to produce any antigen-specific IgG2a and IgG2b immunoglobulins, two Th1-specific antibody classes. 47 The previous finding in mice that IL-4 was able to suppress IgG2a and IgG2b class-switching provides a convincing explanation for this observation. 53 We predict that the altered antibody class profile following enhanced GR signaling may significantly influence the quality of an immune response.…”
Section: Discussionmentioning
confidence: 81%
“…However, the effects of these disease-modifying drugs and immunosuppressant on airway hyperresponsiveness and asthma were controversial. A few experimental studies demonstrated the attenuation of allergen-induced airway inflammation and sensitization after long-term use of leflunomide 32,33 . In addition, immunosuppressant was suggested to relieving asthma by inhibition of T cell activation 34 .…”
Section: Discussionmentioning
confidence: 99%